2005
DOI: 10.1063/1.2058207
|View full text |Cite
|
Sign up to set email alerts
|

Angular dependence of the magnetization reversal in exchange-biased Fe∕MnF2

Abstract: A detailed study of exchange-biased Fe/MnF 2 bilayers using magneto-optical Kerr Effect shows that the magnetization reversal occurs almost fully through domain wall nucleation and propagation for external fields parallel to the exchange bias direction.For finite angles φ between bias and external field the magnetization is aligned perpendicular to the field cooling direction for a limited field range for decreasing fields.For external fields perpendicular to the bias direction the magnetization aligns with th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
25
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 15 publications
2
25
0
Order By: Relevance
“…While at high temperature, the critical t AFM increases, the peak of H eb moves to higher t AFM and gradually disappear 10 . Compared to the extensive investigation on polycrystalline EB systems, there are only a few works focused on epitaxial films 11,12 . Thanks to the clear AFM/FM interface and the well-controlled magnetic configuration near the AFM/FM interface, the epitaxial exchange biased bilayers is regarded as the ideal systems for investigating the underlying physics of exchange bias, and have attracted much attention in the recent years 13 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While at high temperature, the critical t AFM increases, the peak of H eb moves to higher t AFM and gradually disappear 10 . Compared to the extensive investigation on polycrystalline EB systems, there are only a few works focused on epitaxial films 11,12 . Thanks to the clear AFM/FM interface and the well-controlled magnetic configuration near the AFM/FM interface, the epitaxial exchange biased bilayers is regarded as the ideal systems for investigating the underlying physics of exchange bias, and have attracted much attention in the recent years 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Considering both K eb and K u , the value of EB and coercivity for the polycrystalline EB systems can be numerically fitted by the Stoner-Wohlfarth model 18 . In epitaxial EB systems, the intrinsic magnetocrystalline anisotropy needs to be further considered, which results in multi-step hysteresis loops and a complex angular dependent behavior 11,12,14 . An effective field model, which considers the contributions to the effective field acting on the FM layer during magnetization reversal, was developed by Arenholz et al, to quantitatively interpret the complicated angular dependent switching fields 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arenholz et al 8 and Tillmanns et al 9 have observed that in twinned Fe/MnF 2 films, the shape of a kinked hysteresis loop evolves sensitively with the angle between the measurement and bias fields. Other studies have examined the dependence of the magnetization reversal mechanism on the exchange field and anisotropy fields in the samples.…”
mentioning
confidence: 99%
“…10,15 We have recently shown in FeF 2 and MnF 2 based systems that the switching mechanism depends on the AF crystallinity, especially on the alignment of the applied field with respect to the AF anisotropy axes. 9,16,17 For example, FM/epitaxial-FeF 2 thin films have a single AF spin axis along which the exchange field would also point. With a small misalignment ͑ϳ2°͒, the switching is clearly dominated by rotation.…”
mentioning
confidence: 99%